Formidling av det fragmenterte: Et nettleksikon for norsk musikkdramatikk - Skagen, Annabella; Svendsen, Trond Olav (Teatervitenskapelige studier, 2025)
Mediating the Fragmented: A Digital Compendium of Norwegian Musical Drama The development of musical drama in Norway took place during specific cultural and economic conditions which contributed both to a sporadic performance tradition and a number of unfinished or unperformed works. The history of musical drama in Norway, then, is partly a history of that which did not take place. The field’s archival situation remains partly opaque, with music scores, libretti, and other source materials dispersed across libraries, archives and museums; in private ownership or presumed lost. This has had historiographic consequences both for the perspective of theatre and music history studies, as well as for the performing arts. The recently founded Society for Norwegian Musical Drama Heritage (FNMA) has initiated the creation of a digital compendium to increase the accessibility of established knowledge as well as of the historical source materials of Norwegian musical drama from the mid-1750s up to the 2nd World War. Taking as their starting point an understanding of the dispersed history of musical drama – performed and unperformed – as an unarranged archive, or reservoir, the authors discuss the potential of a digital compendium as a cultural heritage tool.